MANAJEMENT OF MIDWIFERY CARE DURING THE POSTPARTUM PERIOD WITH PRE-ECLAMSIA IN CLINIK PRATAMA KASIH BUNDA 2026 - tesyaledistribrsibarani; valensia sidabutar; siti fadhilla; yesica geovany sianipar; lona melati lumbantobing (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: The postpartum period is the period after childbirth until the reproductive organs return to their pre-pregnancy condition and is a phase that is vulnerable to various complications, one of which is postpartum preeclampsia. Continuity of midwifery care emphasizes promotive and preventive efforts, early detection of complications, and counseling to improve maternal and child health (Munthe et al., 2019). Objectives: This paper aims to identify and understand the management of midwifery care for postpartum mothers with preeclampsia, including risk factors, signs and symptoms, diagnosis, management, and the role of midwives in early detection and prevention of complications. Methods: The method used was a literature review by examining various relevant scientific sources, including midwifery textbooks, research articles, and clinical practice guidelines related to postpartum preeclampsia. Results: The review findings indicate that postpartum preeclampsia requires close monitoring of blood pressure, proteinuria, and signs of organ dysfunction. Midwifery care management includes comprehensive assessment, problem identification, maternal condition monitoring, health education, collaboration with other healthcare professionals, and the application of Varney’s seven-step midwifery management process to prevent complications. Conclusions: Comprehensive, continuous, and evidence-based midwifery care plays an important role in improving the safety of postpartum mothers with preeclampsia, preventing complications, and supporting maternal recovery during the postpartum period.